Inoculação biológica e fertilização fosfatada: estratégias integradas para o cultivo sustentável da mandioca branquinha - MORAES, Lídia Ferreira (2024)
Among the crops that are most produced and consumed in Brazil is cassava (Manihot esculenta Crantz) belonging to the Euphorbiaceae family, therefore sustainable practices are increasingly required, such as inoculation which consists of the use of biofertilizers that are formulated from microorganisms such as Bacillus megaterium, as well as the use of appropriate fertilizers to increase productivity. The objective was to evaluate the agronomic characteristics, nutritional status and productivity of cassava plants cv. Branquinha in dryland, inoculated with B. megaterium associated with phosphate fertilizer. The experiment took place between February 2023 and February 2024, it was carried out on a rural property in the municipality of Chapadinha-MA. The cultivar used was cassava cv. Branquinha under rainfed cultivation, planted in holes with dimensions of 10 x 10 x 10 cm, and spacing of 1.0 m x 1.0 m. The experimental design adopted was in randomized blocks, with a 4 x 3 factorial arrangement, (four doses of B. megaterium [D0: 0; D1: 1.0; D2: 2.0; D3: 3.0 L. ha-1 ] applied in the planting furrow and three doses of phosphate fertilizer [P0: 0% - without phosphate fertilizer; P50: 50% and P100: 100% of the recommendation and control], with five replications, totaling 60 plots. The variables analyzed were: plant height; height of the first branch; plant diameter; total productivity; commercial root productivity; non-commercial root productivity; average weight of tuberous roots; average aerial part weight; average weight of commercial roots; root drymatter; aerial part dry matter; harvest index; microbial nitrogen; microbial carbon and soil basal respiration and leaf macro- and micronutrients. For statistical analysis, the hypothesis of normality was carried out, using the Kolmogorov-Smirnov test, with a significance level of 5%. After confirming normality, analysis of variance and the Tukey test were carried out. For significant effect, the data were explored through regression, and a Pearson analysis was carried out at 5% probability. There was a significant effect for the variables: plant height; plant diameter; number of commercial roots per plant; average weight of commercial roots; dry root mass; dry mass aerial part; total productivity; commercial root productivity; number of commercial roots per plant; average weight of commercial roots; microbial nitrogen; microbial carbon; basal breathing; N; P; K; Ca; B; Fe; Mn and Zn. It is concluded that the dose of Bacillus megaterium inoculant of 2 L. ha-1 together with the proportions of phosphate fertilizer at 50 and 100% of the recommendation positively influences the biometrics and productivity of commercial roots of cassava plants, therefore, the lower dose is recommended. The use of Bacillus megaterium in conjunction with the proportions of phosphate fertilizer does not influence the biology of the soil and the nutritional status of cassava leaves (Manihot esculenta Crantz) cv. Branquinha under rainfed cultivation.